Public health: a forgotten piece of the adaptation law puzzle - Boocock, Jennifer; McDonald, Jan; McCormack, Phillipa C. (Frontiers in Climate, 2024)
This paper uses the problem of extreme heat to illustrate the inadequacy of laws for protecting public health under climate change. Climate change is already having serious effects on public health. The Intergovernmental Panel on Climate Change (IPCC) Sixth Assessment Report highlights significant adaptation gaps for human health protection, urging that public health adaptation must be 'proactive, timely and effective.'The law can be a powerful tool for advancing adaptation to protect public health, but there has been very little scholarly analysis of its potential, or whether in some circumstances it may promote maladaptation. For example, legal regimes for land use planning typically respect existing uses of property and make retrofitting for climate-proofing hard to mandate. These regimes can take many years to amend so new infrastructure continues to comply with outdated approaches, such as relying on air conditioning for cooling and offering limited shading. Laws also promote a focus on crisis management during a heat event but fail to promote the preventive action necessary to foster resilience.We present a case study of how the law exacerbates public health risks from extreme heat and falls short of facilitating adaptation in the Greater Western Sydney region of Australia, an area with a population of 2.6 million. In 2019, this area experienced a record near-surface air temperature of 52°C (125.6°F) causing significant adverse physical and mental health impacts. The public health impacts of extreme temperatures in this region are well documented, as are the increasing strains on emergency and health services. This case study demonstrates that laws could help to control heat in the landscape and secure the safety of vulnerable populations, but to do so they must prioritise adaptation to the health impacts of climate change.